Joseph Priestley e Immanuel Kant: un confronto sui temi della libertà e dell’anima (Itinera, 2013)
The paper focuses on the issues of freedom and soul of the human being in relation to the thinking of Joseph Priestley, scientist and philosopher, exponent of English empiricism and materialism schools of the second half of ’700. Recalling the considerations that Immanuel Kant proposed within the first two Critiques, the analysis illustrates both the similarities and the differences that emerge from the comparison between the two philosophical perspectives.